Relationship Between Sodium Intake, Physical Activity and Stress with the Incidence of Hypertension in Pregnant Women at the Gununghalu Health Center 2023 - Kamilatul Muniroh, Fajri; Nugraheni, Dyan Kunthi; Riyanto, Agus; Mauliku, Novie E.; Budiman, Budiman (Universitas Ibn Khaldun Bogor, 2024)
Hypertension or high blood pressure refers to a condition where blood pressure in the blood vessel system continues to increase (World Health Organization, 2018). Gestational hypertension can have detrimental effects on the mother and fetus, and increase the risk of cardiovascular disease in the future. Women who have experienced preeclampsia or hypertension have higher health risks, including a 7- to 8-fold increased risk of death from coronary artery disease (Subki & et al, 2018). This study aims to investigate the correlation between factors that influence the incidence of hypertension in pregnant women in the area served by the Gununghalu Community Health Center. The research design used was case control, with a population of 1,473 people, where the sample consisted of pregnant women, including 63 of whom had hypertension. Data analysis was carried out using the Chi-Square method and multiple logistic regression analysis to identify factors that influence the incidence of hypertension. The research results show that there is a relationship between sodium consumption and hypertension in pregnant women showing a significance value of 0.007, indicating that there is a significant correlation between stress and the incidence of hypertension in pregnant women with a p value of 0.028. However, no significant relationship was found between physical activity and the incidence of hypertension in pregnant women, with a p value of 0.084. Multivariate analysis shows that sodium consumption is a risk factor for hypertension in pregnant women (p=0.004). It is hoped that all pregnant women will always have a pregnancy check-up with a health worker to avoid risks during pregnancy.